Persistent Post COVID-19 Symptoms and Functional Status after 12-14 weeks of recovery, Tamil Nadu, India, 2021. Issue 5 (May 2022) - Rubeshkumar, Polani; John, Alby; Narnaware, Manish; M, Jagadeesan; Vidya, Fermi; Gurunathan, Rajeshkumar; Ganeshkumar, Parasuraman; Bedi, Gagandeep Singh; Kaur, Prabhdeep
Highlights: Rapid assessment of persistent symptoms after 12-14 weeks of recovery among 1001 participants in a metropolitan city in India. One in four reported at least one symptom 12-14 weeks post recovery Hospitalisation for severe infection, having at least one morbidity were associated with persistent symptoms. Hospitalisation for severe infection was independently associated with severe limitation of activities of daily living post COVID-19 recovery.